Pendampingan Penguatan Literasi bagi Karang Taruna Desa Kandangmas untuk Mewujudkan Kandangmas Sebagai Desa Cerdas - Putri Purwaningrum, Jayanti; Zahro, Nafi’ Inayati; Sutono, Sugoro Bhakti; Yudi Purwoko, Riawan (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Kandangmas Village is one of the fostered villages of Muria Kudus University located in Dawe District, Kudus Regency, where one of the problems is the lack of development of youth organizations. Thus, the community service team intends to carry out activities with the aim of strengthening and improving the skills of youth organizations in literacy, numeracy, and digital literacy, so that it is expected to be able to apply them in the Kandangmas Village Community. The implementation method used in this activity is program socialization, training and application of technology, evaluation, and follow-up. Participants in this activity are members of the Kandangmas Village youth organization. The implementation of this mentoring activity is by providing training to youth organizations regarding the importance of literacy in everyday life. The results achieved from the implementation of this training are increasing the insight and skills of youth organizations regarding literacy, numeracy, and digital literacy, which can then be applied to the wider community to realize Kandangmas Village as a Smart Village that has an impact on the progress of the Indonesian nation.